New Light on the Gold Sword of Major George Wilson. (3rd July 2015) - Southwick, Leslie
Abstract : This paper provides new information on the gold sword awarded to Major George Wilson, 39th Regiment of Foot, in 1800 and on the retailer and silversmith, who were commissioned to provide the token.